Assessment of selected upper limb ranges of motion in violinists during instrument performance - Gol, Halina; Szczechowicz, Jakub (Health Promotion & Physical Activity, 2025)
Objective: Playing an instrument is a significant part of a violinist’s life. Daily, they are exposed to specific, forced positions of the upper limbs while playing. Any injuries or overloading of the musculoskeletal system can adversely affect their ability to perform their profession or pursue their passion for playing the violin. The aim of this study was to determine the ranges of motion of selected upper limb joints in violinists during violin playing. A deeper understanding of the biomechanics of playing the instrument can contribute to the development of increasingly effective rehabilitation protocols, facilitate preventive measures, and support the maintenance of musicians’ health and well-being. Material and methods: Twenty-two violinists were recorded while performing a three-octave G-major scale. After selecting appropriate frames, an assessment of selected ranges of motion was conducted using the Angulus application. Results: The ranges of motion achieved by violinists largely depend on their adopted playing technique. The greatest range of motion amplitude was observed in the sagittal plane in the shoulder joint and wrist joint of the bow-holding upper limb, as well as in the sagittal plane of the wrist joint of the violin-holding upper limb. The smallest ranges of motion were observed in the horizontal plane of the shoulder joint of the bow-holding upper limb and in the sagittal plane of the shoulder joint of the violin-holding upper limb. Conclusions: Violinists work on average within the following ranges of motion: in the shoulder joint of the bow-holding upper limb: S: 0-15-87, F: 74-19-0, T: 0-47-63; in the elbow joint: S: 0-39-95; in the wrist joint: S: 34-0-35, F: 19-0-2. For the violin-holding upper limb, the ranges were: in the shoulder joint: S: 0-31-38, F: 22-6-0; in the elbow joint: S: 0-96-106; in the wrist joint: S: 17-0-25.